Let's analyze your friend's work step-by-step:
Starting with the original equation:
\[ 7x + 2 = 73x - 8 \]
Your friend rewrote it as:
\[ 7(x) + 2 = 7(3x) - 8 \]
From that point, they correctly distributed the terms:
\[ 7x + 2 = 21x - 8 \]
Next, the friend moves all terms involving \( x \) to one side and constants to the other side:
This step appears to be where the error occurs. They should have rearranged the equation as follows:
- Move the \( 21x \) to the left side:
\[ 7x - 21x + 2 = -8 \]
This leads to:
\[ -14x + 2 = -8 \]
- Next, move the \( 2 \) to the right side:
\[ -14x = -8 - 2 \]
Thus:
\[ -14x = -10 \]
- Now, divide by \(-14\) to solve for \( x \):
\[ x = \frac{10}{14} = \frac{5}{7} \]
Therefore, your friend's solution is incorrect.
The correct answer is: This is not correct. The 7 needs to be distributed across all terms when solving.
The specific issue is that they correctly distributed the \( 7 \) but made an arithmetic error in subsequent steps, leading to the incorrect value for \( x \).